2019
DOI: 10.46743/2160-3715/2019.3774
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Coaching as a Tool for Professional Development: Coaches’ Roles and Considerations

Abstract: In this study, we primarily aimed to investigate coaches’ roles and their considerations in shifting coaching roles they perform. Employing a qualitative descriptive research, we conducted semi-structured interview sessions with ten instructional coaches to determine their roles and considerations in shifting roles during coaching English teachers in primary schools. Utilizing Braun and Clarke’s (2006) six-phase approach, we employed thematic analysis to analyse the desired data collected in the study. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Dapatan kajian ini adalah konsisten dengan dapatan kajian semasa mengenai bagaimana pembimbing instruksional bekerjasama dengan guru melalui pelbagai peranan dalam meningkatkan kualiti pengajaran guru (Kho et al, 2019). Peranan daripada SISC+ PLTV dalam kajian ini adalah pelbagai rupa; mereka menyediakan peluang untuk guru RBT untuk menambah baik amalan pengajaran mereka merentas semua kandungan kurikulum dan peringkat, Tahun 4 hingga Tahun 6.…”
Section: Peranan Pembimbingunclassified
See 1 more Smart Citation
“…Dapatan kajian ini adalah konsisten dengan dapatan kajian semasa mengenai bagaimana pembimbing instruksional bekerjasama dengan guru melalui pelbagai peranan dalam meningkatkan kualiti pengajaran guru (Kho et al, 2019). Peranan daripada SISC+ PLTV dalam kajian ini adalah pelbagai rupa; mereka menyediakan peluang untuk guru RBT untuk menambah baik amalan pengajaran mereka merentas semua kandungan kurikulum dan peringkat, Tahun 4 hingga Tahun 6.…”
Section: Peranan Pembimbingunclassified
“…Seorang SISC+ PLTV menggambarkan peranannya sebagai "memakai pelbagai topi." Ini selaras dengan penemuan kajian sebelum ini yang mengesahkan pembimbing instruksional mesti membezakan sokongan dan menjadi pemimpin instruksional yang empati, tidak berarah, tidak menilai, pelaksana amalan pengajaran baharu, penyokong perubahan, dan pendidik (Kho et al, 2019. Kajian sebelum ini menegaskan bahawa peranan pembimbing instruksional bukanlah sebagi seorang penilai tetapi seorang yang objektifnya adalah untuk menyokong dan mendorong guru untuk menjadi guru yang lebih baik (Wang, 2017). SISC+ PLTV bukanlah penilai; mereka adalah agen perubahan yang menyokong pelaksanaan berkesan bagi program sedia ada dan berasaskan kepada amalan pengajaran guru RBT.…”
Section: Peranan Pembimbingunclassified
“…The complex nature of coaching challenges ICs professionally as it requires them to deal not only with teachers' resistance, acceptance and expectations, but also to adhere to the complex roles that they are bearing. Studies revealed that ICs are expected to adhere to three different roles that are implementer, advocate and educator [5][6][7][8][9][10]. This means that coaches have to engage in the roles depending on the context of the coaching situation and that different strategies need to be employed based on the consideration of the role they chose.…”
Section: Introductionmentioning
confidence: 99%
“…This means that coaches have to engage in the roles depending on the context of the coaching situation and that different strategies need to be employed based on the consideration of the role they chose. Roleshifting constantly occurs depending on the situation [10]. For instance, teachers' stages of learning are different from one individual to another in terms of their ability to reflect and make improvements to their teaching, and because of this, coaches need to adhere to multiple roles to make sure the teaching quality is enhanced [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation